Development of a fuel efficient hybrid engine towards green technology - Rahman, Mohammed Ataur; Asrar, Waqar; Ihsan, Sany Izan; Hossain, Altab; Abdullah, Kassim (2010)
The main focused of this study is to develop a fuel efficient and zero tail pipe emission hybrid engine to operate the designed and developed Urban car of weight 1.42 kN. The hybrid engine is developed by coupling a high efficient 12 volt generator with a 33.5 cc engine of power 1.18 kW @7000 rpm. The generator is activated from the battery power before start the engine in order to turn the armature into an electromagnet. Once start the engine, the battery is disconnected from the generator. The generator starts to power the DC motor to propel the car as soon as started the engine. The engine optimum speed is considered to be 4000 rpm to operate the generator to power the DC motor for propelling the car on 0% slope. While, it is operated at 6000 rpm to power the vehicle on 33% slope. Two supercapacitors each of 2 Farad are equipped in parallel with the generator in order to maintain the constant power supply to the DC motors for propelling the car with speed of 35 km/h. The hybrid engine was run at 65% efficiency which is 118% more than the conventional IC engine.